Measurement Without Theory - Koopmans, Tjalling C. (The Review of Economics and Statistics, 1947)
W HEN Tycho Brahe and Johannes engaged in the systematic labor of measuring the positions of the planets, and charting their orbits, they started with conceptions and models of the planetary system which later proved incorrect in some aspects, irrelevant in others. Tycho always, and initially, believed in uniform circular motion as the natural basic principle underlying the course of celestial bodies. Tycho's main contribution was a systematic accumulation of careful measurements. Kepler's outstanding success was due to a willingness to strike out for new models and hypotheses if such were needed to account for the observations obtained. He was able to find simple which were in accord with past observations and permitted the prediction of future observations. This achievement was a triumph for the approach in which large scale gathering, sifting, and scrutinizing of facts precedes, or proceeds independently of, the formulation of theories and their testing by further facts. The book by Burns and Mitchell,2 discussed here, approaches the problems of cyclical fluctuations in economic variables in the same spirit. The book has two main purposes: first, a detailed exposition, with experimental applications, of the methods of measuring cyclical behavior, developed by the National Bureau of Economic Research; secondly, a search, with the help of these methods, for possible changes in cyclical behavior of economic variables over time, whether gradual, abrupt, in longer cycles, or otherwise. The approach of the authors is here described as in the following sense: The various choices as to what to look for, what economic phenomena to observe, and what measures to define and compute, are made with a minimum of assistance from theoretical conceptions or hypotheses regarding the nature of the economic processes by which the variables studied are generated. In fact, Burns and Mitchell are more consistently empiricist than was. The latter made no secret of his predilection for the principle of circular motion until observations spoke decisively for the elliptical orbit. He held other speculative views as to the role of the five regular solids and of musical intervals in the proportions of the planetary system, which now appear as irrelevant. Burns and Mitchell do not reveal at all in this book what explanations of cyclical fluctuations, if any, they believe to constitute plausible models or hypotheses. The undertaking commands respect, and the precedent holds great promise: For, in due course, the theorist was inspired to formulate the of attraction of matter, which contain the of planetary motion discovered by as direct and natural consequences. The terms empirical regularities and fundamental laws are used suggestively to describe the Kepler stage and the Newton stage of the development of celestial mechanics. It is not easy to specify precisely what is the difference between the two stages. Newton's of gravitation can also be looked upon as describing an regularity in the behavior of matter. The conviction that this law is in some sense more fundamental, and thus constitutes progress over the stage, is due, I believe, to its being at once more elementary and more general. It is more elementary in that a simple property of mere matter is postulated. As a result, it is more general in that it applies to all matter, whether assembled in planets, comets, sun or stars, or in terrestrial objects thus explaining a much wider range of phenomena. It appears to be the intention of Burns and 'This article will be reprinted as part of Cowles Commission Papers, New Series, No. 25. I am indebted to several friends, including Dr. A. F. Burns, for comments on an earlier draft. These comments have helped me to bring out more clearly the issues raised in this review, for which, of course, I remain exclusively responsible. T.C.K. 2Arthur F. Burns and Wesley C. Mitchell, Measuring Business Cycles (National Bureau of Economic Research, Studies in Business Cycles, No. 2, New York, I946).